مجلة الدراسات الإسلامية والفكر للبحوث التخصصية - Abdullah Hamad Saeed Al Junaibi; Adnan bin Mohammad Yusof; Najm Abdulrahman Khalaf; Muhammad Mustaqeem bin Muhammad Zarif (The Scientific Institute for Advance Training and Studies (SIATS), 2024)
Non-Indexed Publication